Systemic and Local Administration of Antimicrobial and Cell Therapies to Prevent Methicillin-Resistant Staphylococcus epidermidis-Induced Femoral Nonunions in a Rat Model - Arianna B. Lovati; Lorenzo Drago; Marta Bottagisio; Matilde Bongio; Marzia Ferrario; Silvia Perego; Veronica Sansoni; Elena De Vecchi; Carlo L. Romanò (Mediators of Inflammation)
S. epidermidis is responsible for biofilm-related nonunions. This study compares the response to S. epidermidis-infected fractures in rats systemically or locally injected with vancomycin or bone marrow mesenchymal stem cells (BMSCs) in preventing the nonunion establishment. The 50% of rats receiving BMSCs intravenously (s-rBMSCs) died after treatment. A higher cytokine trend was measured in BMSCs locally injected rats (l-rBMSCs) at day 3 and in vancomycin systemically injected rats (l-VANC) at day 7 compared to the other groups. At day 14, the highest cytokine values were measured in l-VANC and in l-rBMSCs for IL-10. µCT showed a good bony bridging in s-VANC and excellent both in l-VANC and in l-rBMSCs. The bacterial growth was lower in s-VANC and l-VANC than in l-rBMSCs. Histology demonstrated the presence of new woven bone in s-VANC and a more mature bony bridging was found in l-VANC. The l-rBMSCs showed a poor bony bridging of fibrovascular tissue. Our results could suggest the synergic use of systemic and local injection of vancomycin as an effective treatment to prevent septic nonunions. This study cannot sustain the systemic injection of BMSCs due to high risks, while a deeper insight into local BMSCs immunomodulatory effects is mandatory before developing cell therapies in clinics.